Isu Penyelewengan Tafsiran Ayat Al-Quran oleh Samina Ali dalam Saluran TEDx Talk: The Issue of Quranic Verses Misinterpretation by Samina Ali in the TEDx Talk Channel - Razzak, Monika @ Munirah Abd (Al-Bayān, 2022)
Abstract The modernity that occurs in Information Technology has resulted in the dumping of information in the digital world. This is inevitable as the use of technology in the millennium period has become essential for all parties. At the same time, the development of new media has also increased, and It has left an impact on society globally. Information greatly influences cultures, beliefs -especially religious beliefs-, ideologies, thoughts, value systems, behaviours and social interactions. This study discussed the issues raised by Samina Ali in the TEDx Talks channel. The methodology used was a qualitative design using content analysis as the data analysis method. The results of this study showed that the interpretation presented by Samina Ali is in direct contradiction to the interpretation agreed upon by authoritative scholars. Therefore, Muslims need to be more cautious in seeking information about Islam in the TED Talks YouTube channel as not everyone is qualified to speak about religion without expertise and authority in that field.